Musculoskeletal Health in Pregnancy and Postpartum An Evidence-Based Guide for Clinicians - Fitzgerald, Colleen M.; Segal, Neil A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Providing clinicians with a comprehensive, evidence-based summary of musculoskeletal health in pregnancy and postpartum, this is the first book of its kind to describe the physiologic changes, prevalence, etiology, diagnostic strategies, and effective treatments for the most common musculoskeletal clinical conditions encountered during this phase of life. Lumbopelvic pain, upper and lower extremity diagnoses, labor and delivery considerations, including the impact on the pelvic floor, and medical therapeutics will be discussed. Additionally, the importance and influence of exercise in pregnancy, the long-term implications of musculoskeletal health in pregnancy and current and future directions for research will be addressed. The childbearing period is a time of remarkable reproductive and musculoskeletal change, predisposing women to potential injury, pain, and resultant disability. Musculoskeletal Health in Pregnancy and Postpartum offers musculoskeletal medicine specialists, obstetricians and any clinicians involved in the care of pregnant or postpartum women the tools necessary to prepare for, treat and prevent these concurrent injuries during an already challenging time.
Musculoskeletal Anatomic, Gait, and Balance Changes in Pregnancy and Risk for Falls -- Hormonal Influence on the Neuromusculoskeletal System in Pregnancy -- Musculoskeletal Imaging in the Pregnant and Postpartum Patient -- Diagnosis of Pelvic Girdle Pain -- Treatment, Bracing and Modalities in Pelvic Girdle Pain -- Neural Injury during Pregnancy and Childbirth -- Interventional Procedures for Musculoskeletal Pain in Pregnancy and Postpartum: Efficacy and Safety -- Hip Disorders in Pregnancy -- Upper Limb Issues in Pregnancy and Postpartum: Carpal Tunnel Syndrome and DeQuervain$1 (Bs Tenosynovitis -- Labor and Delivery Considerations: Pubic Symphysis Separation, Fractures Associated with Transient Osteoporosis of Pregnancy, Sacral Stress Fractures and Coccydynia/Coccyx Fracture -- Pelvic Floor Injury and Consequences -- Pelvic Floor Myofascial Pain and Dysfunction -- Pelvic Pain after Cesarean Section -- Pharmacological Treatment of Musculoskeletal Conditions during Pregnancy and Lactation -- Exercise in Pregnancy and Postpartum -- Epilogue: Where to go from here$1! =(BFuture Research.s
Keywords: Medicine; Obstetrics; Rheumatology; Orthopedics; Medicine & Public Health; Orthopedics; Obstetrics/Perinatology.; Rheumatology; Electronic books